Export upgrading and environmental performance: Evidence from China. Issue 86 (November 2017) - Mao, Xiyan; He, Canfei
Highlights: Explores the disjuncture between export upgrading and environmental performance. Export upgrading in China benefits the environment via changing product mix. Specialisation in polluting production encourages the structural transformation. Stringent environmental regulation protects the greening efforts of upgrading. Environmental upgrading should shift from being performance- to process-oriented. Abstract: This study argues that export upgrading can, but does not necessarily, lead to environmental improvement. A synergy between global and local linkage determines the likely disjuncture between export upgrading and environmental improvement. On the basis of the panel data covering 261 prefectural-level cities in China during 2003–2011, this study applies the decomposition of export sophistication to quantify diverse upgrading types. It also divides the sample cities into groups and uses the fixed-effect regression by groups to investigate the role of local linkages. Empirical findings indicate that environmental improvement associated with export upgrading in China has largely relied on changing product mix to avoid environmental costs, exhibiting a significant displacement effect. The role of efficiency promotion of production process is still insignificant. Local linkage may alter the environmental effects of export upgrading. Specialisation in polluting production can help cities to change product mix through the agglomeration of related firms. Stringent environmental regulation protects cities from the export–environment disjuncture through imposing additional costs. These findings suggest that the greening efforts of China should take one step further from export restructuring to efficiency promoting.